NUEVOS BIOMATERIALES Y MÉTODOS PARA EL DEFECTO DE HUESO CRANEOFACIAL: INJERTOS DE HUESO CONDROIDE EN HENDIDURAS ALVEOLOMAXILARES - Sueldo R., Efrain (2000)
The purpose of this study was to evaluate autogenous osteogenic marrow within chondroid bone grafts in simulated alveolar defects of mice in order to determine the ability of the graft material effectively close the cleft from an osseous standpoint and to observe the effect of the grafting procedure. Critical-sized defects were made in the premaxillary bones of male mice using a surgical trephine and a low - speed dental engine as a model of the maxillary alveolar cleft for testing bone - inductive agents. Premaxillary trephine defects were not repaired by fibrous tissue or bone formation 30 days after operation. This nonhealing bony wound of the premaxilla in mice may be useful as a model for studying the effect of bone-inductive agents on the healing of alveolar cleft. Distraction osteogenesis is a recently advanced principle of bone lengthening in which a long bone separeted by osteotomy is subjected to slow progressive distraction using an external fixation device. The osteotomy site was surrounded by an external callus consisting of hyaline cartilage. The callus contained a lot of chondroid bone. The transplant bone within chondroid bone was characterized by bone formation and remodeling 30 days after transplantation. Throughout the experiment, our finding demostrated, for the first time, that the transplant bone that contains chondroid bone may be used clinically in relation to craniofacial bone defects to improve the treatment of bone grafts.